Association of human carboxypeptidase E exon5 gene polymorphisms with angiographical characteristics of coronary atherosclerosis in a Chinese population - Wang Jie; Zhang Yun; Yang Zhi-jian; Zhu Tie-bing; Wang Lian-sheng; Chen Bo; Cao Ke-jiang; Huang Jun; Ma Wen-zhu; Jia En-zhi (Acta Pharmacologica Sinica, 2016)
Aim: To explore the association between 801C>T and 847C>T polymorphisms of the human carboxypeptidase E (CPE) gene exon5, which could cause hyperproinsulinemia, and the angiographical characteristics of coronary atherosclerosis. Methods: In total, 1044 consecutive patients who underwent coronary angiography for suspected or known coronary atherosclerosis were examined with respect to their genotypes, insulin, proinsulin level, and other risk factors of coronary atherosclerosis. The angiographical characteristics of coronary atherosclerosis (ie the severity of coronary heart disease) were defined by Gensini's score (GS) system. Results: The results showed that the genotype frequencies of CC, CT, and TT at 801C>T locus were significantly different among the patients of the 4 groups who were classified by quartile values of GS (P=0.033). However, the frequency of the 847T allele was 0 for all the patients. The ordinal logistic regression analysis revealed that the increased risk of angiographical characteristics of coronary atherosclerosis were associated with CPE 801CT/TT variant genotypes [adjusted odds ratio (OR)=1.23, 95% confidence interval (CI) =0.93-1.63 for 801CT and adjusted OR=3.13, 95% CI=1.18–8.28 for 801TT] compared with the 801CC wild-type homozygotes. A stratification analysis showed that the effects of the CPE 801TT genotype were more evident among subgroups with relatively older (>=60 years) patients, males, and smokers. Furthermore, an analysis of covariance controlling age, sex, and body mass index indicated that differences of blood glucose, insulin, insulin resistance, and the proinsulin level between 801C>T genotype groups were not statistically significant. Conclusion: These findings indicate that the 801C>T polymorphism in the CPE exon5 gene may contribute to the angiographical characteristics of coronary atherosclerosis in the Chinese population.